Factors Affecting Academic Self-efficacy of Syrian Refugee Students: A Path Analysis Model - Halil Sarı; Hasibe Yahsi Sari; Selahattin Gelbal (International Journal of Assessment Tools in Education, 2020)
In this study, the effect of resilience, perceived social support, life satisfaction and self-regulation variables on the academic self-efficacy of Syrian refugee undergraduate students were examined with a path analysis model. The sample consisted of Syrian undergraduate students living in Turkey. The sample of the research was randomly selected and participation was voluntarily. Data collection tools used were demographic information form, Arabic versions of academic self-efficacy, resilience, perceived social support, life satisfaction and self-regulation scales. In the data analysis, self-regulation and perceived social support selected as the exogenous variables, academic self-efficacy was selected as the endogenous variable, and resilience and life satisfaction were selected as the mediator variables. In the study, the direct and indirect effects from exogenous variables to academic self-efficacy were examined. The findings of the research revealed that self-regulation and perceived social support directly affected academic self-efficacy, life satisfaction had a mediating effect on perceived social support, and resilience had self-regulation. It is concluded that in order to increase the academic self-efficacy of refugee students, self-regulation and social support from the society should be increased, as well as life satisfaction and resilience against difficulties.